Shame and Alienation in Kafka’s The Metamorphosis - Karla Sharin Minar; Anton Sutandio (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This article explores Sartre’s concept of shame and alienation in Kafka’s The Metamorphosis through the portrayal of the protagonist. By focusing on the interpretation of the characteristics of Gregor Samsa through New Criticism approach, this article reveals that shame and alienation may occur when a person realizes that one is judged by others and sees oneself through the eyes of others. This way of looking at one’s identity is problematic because it creates complexity within the existence of the self. Through his fantastical transformation into an insect, Gregor cannot help but seeing himself from his family’s point of view. Instead of fighting for himself, he is made to believe that he deserves to be alienated. From the analysis of the protagonist, it is revealed that his being selfess and dutiful in a way trigger the shame and alienation that result in his submission to death. Keywords: alienation, Kafka, Sartre, shame